Changes in the composition of urine over six hours using urine dipstick analysis and automated microscopy - Pranav C. Parikh; Serena D. Souza; Wassim Obeid (BMC Nephrology)
Abstract Background Urinalysis is a commonly performed test for the diagnosis and prognosis of kidney disease in hospitalized patients. It involves examining the chemical composition of the urine and microscopy to examine the cells and casts. In clinical settings, urinalysis is frequently delayed by several hours after sample collection and held at room temperature. The purpose of this study is to investigate the changes in urine composition over set time intervals to confirm the reliability of urinalysis when there are delays in performing the tests. Methods We obtained 15 mL of urine from the Foley catheters of five patients in the intensive care unit. We utilized the state-of-the-art IDEXX SediVue Dx ® machine to perform urine microscopy and the Siemens CLINITEK Status + Urine Analyzer to perform the dipstick tests. We performed microscopy and dipstick tests at 0, 1, 2, 4, and 6 h. Between the two testing methods, 30 individual components were tested in the urine. We calculated the %CV for each component by taking four repeated measurements at one time period for multiple samples. Results After calculating the %CV for each component, we analyzed the trend for each constituent over the 6 h. If the percent change over the six-hour interval was ± twofold than the %CV, we determined time to influence the results. Significant changes were seen in bacteria as the levels increased, red blood cells and pathological casts where the level decreased, and crystal levels were determined inconclusive due to fluctuations in the results. All other components were found to remain unchanged. Conclusions Timely urine analysis is necessary for accurate results as delayed analysis can considerably change the makeup of urine, which can affect clinical decisions and patient management.